Coronary in-stent restenosis in a real-world repeat-angiography cohort: frequency and clinical correlates from western kazakhstan (Bangladesh Journal of Medical Science, 2026)
Background Coronary in-stent restenosis (ISR) remains clinically relevant in routine practice and is often detected in patients returning for repeat coronary angiography after prior percutaneous coronary intervention (PCI). Objective To determine the frequency of angiographically confirmed ISR and identify associated clinical and laboratory characteristics, including left ventricular ejection fraction (LVEF), in a real-world repeat-angiography cohort . Methods This multicenter retrospective registry included 1,005 adults from three PCI centers in Aktobe region (Kazakhstan) who underwent repeat coronary angiography in 2019-2023 and had a documented history of prior stent implantation. ISR was defined as ≥50% diameter stenosis within a previously implanted stent. Groups with and without ISR were compared using nonparametric and categorical tests; multivariable logistic regression assessed independent associations. Results ISR was identified in 138/1,005 patients (overall frequency 13.7%). Patients with ISR more often had diabetes, peripheral artery disease, prior CABG, and heart failure history, and more frequently underwent angiography in the setting of myocardial infarction. ISR was associated with higher creatinine and a higher prevalence of eGFR